Single colour one‐shot scan using modified Penrose tiling pattern - Hiroshi Kawasaki; Hitoshi Masuyama; Ryusuke Sagawa; Ryo Furukawa (IET Computer Vision, 2013)
In this study, the authors propose a new technique to achieve one‐shot scan using single colour and static pattern projector; such a method is ideal for acquisition of moving objects. Since projector–camera systems generally have uncertainties on retrieving correspondences between the captured image and the projected pattern, many solutions have been proposed. Especially for one‐shot scan, which means that only a single image is required for shape reconstruction, positional information of a pixel of the projected pattern should be encoded by spatial and/or colour information. Although colour information is frequently used for encoding, it is severely affected by texture and material of the object and leads unstable reconstruction. In this study, the authors propose a technique to solve the problem by using geometrically unique pattern only with black and white colour that further considers the shape distortion by surface orientation of the shape. The authors technique successfully acquires high‐precision one‐shot scan with an actual system.